Historia de las islas Marianas - Morales, Luis de, 1641-1716; Le Gobien, Charles, 1653-1708 (Crónicas y memorias., 2013)
Morales' "Historia de las islas Marianas" seems to predate Le Gobien's "Historie des isles Marianes" and was probably used as the basis for Le Gobien's work. Le Gobien attributed some of the investigative work for his book to Morales but the editor makes the case that the opposite was true